Fabrication of micro-optical connectors for electro-optical sensor devices by a combined femtosecond laser system. (5th February 2021) - Epifanov, E O; Tarkhov, M A; Timofeeva, E R; Trofimov, I V; Asharchuk, I M; Obydennov, D V; Li, Weichang; Gonchukov, S A; Minaev, N V
Abstract: The article demonstrates the fundamental possibility of creating microstructures for various functional purposes using the capabilities of the two-photon femtosecond polymerization method. The developed technological approach for creating a micro-optical holder for standard single-mode and multimode fibers is demonstrated. This type of holder can be used to manufacture a unit for optical matching of optical fibers with sensitive optical elements. The possibility of optical matching of fibers with a superconducting single-photon detector, an array system of bolometric superconducting microbridges, and spherical self-formed microlenses by near infrared-sensitive photopolymerization has been experimentally shown. The device manufacturing process was carried out in a combined single laser micromachining facility using femtosecond laser radiation for lithography with submicron resolution, texturing of the sensor surface, and the formation of microstructures for installing single-mode optical fibers.